2008
DOI: 10.1093/tropej/fmn050
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 3-Day Amoxycillin vs. 5-Day Co-trimoxazole in the Treatment of Non-severe Pneumonia in Children Aged 2-59 Months of Age: A Multi-centric Open Labeled Trial

Abstract: This cluster randomized, open labeled trial was conducted to compare the effectiveness of 3 days of oral amoxycillin and 5 days of co-trimoxazole treatment in terms of clinical failure in children with World Health Organization (WHO) defined non-severe pneumonia in primary health centers in rural India. Participants were children aged 2-59 months with WHO defined non-severe pneumonia, with or without wheeze, who were accessible to follow up. From seven primary health centers in each arm, 2009 cases were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 14 publications
3
48
0
2
Order By: Relevance
“…Similarly, a cluster randomized multicentric study [49] with over 2000 children (2-59 months) with WHO defined non-severe pneumonia reported wheezing in 22%, despite excluding recurrent respiratory distress. The CATCHUP multicentric RCT [119] in Pakistan recorded wheezing in 10.9% children (2-59 months) with non-severe pneumonia.…”
Section: Frequency Of Wheezingmentioning
confidence: 97%
“…Similarly, a cluster randomized multicentric study [49] with over 2000 children (2-59 months) with WHO defined non-severe pneumonia reported wheezing in 22%, despite excluding recurrent respiratory distress. The CATCHUP multicentric RCT [119] in Pakistan recorded wheezing in 10.9% children (2-59 months) with non-severe pneumonia.…”
Section: Frequency Of Wheezingmentioning
confidence: 97%
“…The low prevalence of wheezing in this study was because of a two stage screening procedure resulting in exclusion of children with recurrent respiratory distress, and also those in whom 'fast breathing' disappeared after an initial course of bronchodilators. In another recent multicentric study enrolling more than 2000 underfive children from rural primary health centers in India, wheezing was documented in 22% of children having WHO defined non-severe pneumonia, despite excluding cases with recurrent respiratory distress (5). In children having lower chest indrawing (categorized as severe pneumonia as per WHO definition), the prevalence of wheezing is even higher.…”
Section: How Common Is Wheezing In Ari?mentioning
confidence: 99%
“…51 Moreover, several comparative studies showed equivalent treatment results between different types, doses, and administration forms of antibiotics in children with IMCI-defined pneumonia. [52][53][54] Treatment failures of serious pneumonia were primarily related to infants (3-11 months) with very fast breathing, chest indrawings and hypoxia 10,11,53 and long-term cough, 10 but were not associated with fever, 10,11,54 raising questions concerning the diagnosis of bacterial pneumonia according to BTS guidelines.…”
Section: Over-diagnosis Of Bacterial Pneumoniamentioning
confidence: 99%